2021
DOI: 10.1111/jfpp.15340
|View full text |Cite
|
Sign up to set email alerts
|

Ergothioneine accumulated in the catfish muscle by supplementation of Flammulina velutipes extract prevents lipid oxidation, improves color stability, and limits soft structure of the fillet during frozen storage

Abstract: This study aimed to evaluate whether ergothioneine (ESH) accumulated in catfish muscle affected to fillet quality during frozen storage. The fish after fed by feed supplemented 0 to 15% concentrated extract (CE) from Flammulina velutipes for 30 days were filleted and stored at −18 ± 0.2°C for 90 days. The results show that with 10% CE, the highest accumulation of ESH in fish muscle was 21.02 mg/Kg. During preservation, ESH decreased gradually with DPPH. Peroxide and FFA were the lowest value at 1.09 meq/Kg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 50 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…Recently, Deepitha et al. (2021) prepared Padina tetrastromatica seaweed extract to improve the quality of pangasius fillets via soaking. The samples treated with 2% extract had the extended shelf‐life, especially by preserving the redness of fillets, which was mainly due to inhibition of metMb formation via phenolic present in the extract.…”
Section: Prevention Of Discolorationmentioning
confidence: 99%
“…Recently, Deepitha et al. (2021) prepared Padina tetrastromatica seaweed extract to improve the quality of pangasius fillets via soaking. The samples treated with 2% extract had the extended shelf‐life, especially by preserving the redness of fillets, which was mainly due to inhibition of metMb formation via phenolic present in the extract.…”
Section: Prevention Of Discolorationmentioning
confidence: 99%
“…The sulfur atoms are then combined from cysteine (Ey et al., 2007) and undergo sulfhydration to form ESH (Ashida et al., 2005). The results of this study showed that the ESH concentration reached 592.84 mg/kg, higher than from Flamulina velutipes extract with an ESH content of 512.2 mg/kg (Ha et al., 2021). So, it can be confirmed that A. oryzae is a potential microorganism for ESH biosynthesis at very high levels.…”
Section: Resultsmentioning
confidence: 85%
“…A. oryzae can also synthesize both glutathione and ESH, the two most powerful antioxidants that every microorganism needs. The mechanism of action of ESH is completely different from glutathione, although it is a lesser reducing agent than glutathione, but ESH is described as an effective antioxidant by stabilizing oxygen alone, recovering hydroxyl radicals and inhibiting heavy metal catalytic reactions (Bao et al., 2010; Ha et al., 2021). Depending on the additional inducers in the culturing process and the nutritional requirements of the fungus, A. oryzae secretes enzymes to hydrolyze nutrients such as amino acids as food sources and at the same time biosynthesis BCs that are essential for cell survival and development.…”
Section: Resultsmentioning
confidence: 99%
“…As consumers are increasingly interested in food products associated with animal welfare and concerned with general quality, many studies are working with a multidisciplinary approach to evaluate the effects of new additives that fit these new market demands. For fish fillets or meat in general, one of the most perceivable characteristics is the color, hence, an essential parameter to be analyzed [3,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The results of L* (lightness), a* (redness index) and b* (yellowness index) of fillets were similar to those presented by Ünal Şengör et al [70], that evaluated color of commercial gilthead seabream during cold storage. Whereas no information available about the possible effects of HBP on fish fillet quality and its relationship with the immune response, in a study using a natural compound (Flammulina velutipes extract) in catfish diets, it was observed that the experimental diets prevented lipid oxidation and improved color stability during frozen storage [69].…”
Section: Discussionmentioning
confidence: 99%